PENGEMBANGAN MEDIA BUKU SAKU PENDIDIKAN AGAMA ISLAM BERBASIS MIND MAPPING PADA MATERI ASMA’UL HUSNA KELAS X DI SMA ANNUR BULULAWANG - Zahroh Annisa; Lia Nur Atiqoh Bela Dina; Dian Mohammad Hakim (VICRATINA, 2022)
This research is motivated by student not attractive in learning activities. It is due to the lack of variation in the use of learning media. With this, the existence of innovative and interesting learning media is very much needed. The main purpose of this study was to develop a mind mapping-based pocket book on the material for asthma'ul husna class X at Annur Bululawang High School. The research is using research and development (R&D) method. In this case the researcher uses a simplified borg and gall research model to five steps. The five steps are Observation, Product Design, Product Validation, Product Revision and Product Trial. The result of this research is to produce a product in the form of a good mind mapping-based pocket book learning media and in accordance with the Asma'ul Husna material in Islamic religious education subjects. The students after strongly agreed to study using a mind mapping-based Islamic religious education pocket book on the Asma'ul Husna material. This can be seen from the results of student questionnaires which reached a score of 85%. Based on these values, it can be stated that this media is very valid.